Risks of Stagnation in the Euro Area - Lin, Huidan (Washington, D.C. : International Monetary Fund, 2016)
This paper discusses the risks of stagnation over the medium term in the euro area. It examines the consequences of longer-term growth trends that predate the crisis and the progress made in addressing the crisis legacies of high unemployment and debt. The paper illustrates in a downside scenario, how low potential growth and crisis legacies leave the euro area vulnerable to a negative shock that tips the economy into a prolonged slowdown.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet